Factors Influencing Farmers Decision in Rainfed Areas - P.L. Manohari; G.R. Desai (Journal of Extension Education, 2016)
The study was undertaken to understand the different production factors affecting decision making process of the farmers in rainfed areas of ten states in India. From each state 40 farmers were selected from the lowest rainfall raining areas as respondents. Data were collected using specially designed structured pretested schedule. The results show that in rainfed areas majority of the farmers considered factors related to inputs along with other factors viz., risk bearing ability, agro-climatic conditions and market situation for taking divisions in Agricultural production.